2017
DOI: 10.1016/j.heares.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Performance in noise: Impact of reduced speech intelligibility on Sailor performance in a Navy command and control environment

Abstract: Noise, hearing loss, and electronic signal distortion, which are common problems in military environments, can impair speech intelligibility and thereby jeopardize mission success. The current study investigated the impact that impaired communication has on operational performance in a command and control environment by parametrically degrading speech intelligibility in a simulated shipborne Combat Information Center. Experienced U.S. Navy personnel served as the study participants and were required to monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…Sheffield et al (2016Sheffield et al ( , 2017 showed that operating with a hearing loss can significantly reduce lethality and survivability, and compromise mission success in dismounted combat. And in a precursor to the current study, Keller et al (2016) demonstrated that as speech intelligibility (SI) was reduced, Navy watch standers had difficulty responding to communications directed at them and changed behavior in several ways that could compromise the mission. The general methodology used in these studies was first introduced by Garinther and Peters (1990) to evaluate performance deficits in Army tank crew performance as a function of reduced SI and was later used by Casto et al (2012) in an aviation setting to show changes in performance for Blackhawk simulator pilots.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Sheffield et al (2016Sheffield et al ( , 2017 showed that operating with a hearing loss can significantly reduce lethality and survivability, and compromise mission success in dismounted combat. And in a precursor to the current study, Keller et al (2016) demonstrated that as speech intelligibility (SI) was reduced, Navy watch standers had difficulty responding to communications directed at them and changed behavior in several ways that could compromise the mission. The general methodology used in these studies was first introduced by Garinther and Peters (1990) to evaluate performance deficits in Army tank crew performance as a function of reduced SI and was later used by Casto et al (2012) in an aviation setting to show changes in performance for Blackhawk simulator pilots.…”
Section: Introductionmentioning
confidence: 82%
“…Task 1: Modified Rhyme Test (MRT). An MRT was completed using an adaptive procedure to establish individualized SNRs corresponding to SI levels of 80%, 65% and 50% for each participant using prerecorded stimuli from the study's two confederates (see Keller et al 2016 for details of the adaptive MRT procedure). The MRT is a closed-set speech recognition test originally developed as a more efficient way to evaluate communication systems in the military (House, et al, 1965).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A feasibility study exploring a new model of military hearing care suitable for use in both garrison and deployment settings is due to start imminently and will potentially allow medical officers on the ground access to super subspecialty opinions and support. For unit commanders, this is particularly important in light of recent studies showing the negative effects of temporary hearing impairment on cognition and task performance which occurs in both purely communication-based tasks and in target acquisition 1 2…”
mentioning
confidence: 99%